Influence of SERVQUAL Dimensions (Empathy and Responsiveness) on Patient Satisfaction at Mulawarman University Dental Hospital - Erwin Gunawan; Rohman Daka; Ahmad Setiawan Jarigau; Mutmainnah Lutfi; Imran Irsal (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Mulawarman University Dental Hospital (RSGM Unmul), as a new teaching hospital in East Kalimantan, acts as both oral healthcare services and clinical education. Oral health service utilization of certain populations is still low in East Kalimantan, despite the strategic function of oral health service, it indicates ongoing challenges with regard to access and patient engagement. However, only few studies empirically explore the relationship between specific service management dimensions and patient satisfaction in a dental teaching hospital context, particularly with regard to empathy and responsiveness as related to SERVQUAL. So far, there has been no systematic study at RSGM Unmul,which is obviously an empirical and contextual research gap. Objective: The study aims to determine influence of dental healthcare service management on patient satisfaction at Mulawarman University Dental Hospital Empathy And Responsiveness. Methods: This study had a descriptive-analytic quantitative approach with cross sectional design involving 81 patients in RSGM Unmul that was selected by purposive sampling. Data collection utilized a modified SERVQUAL questionnaire with Likert type responses on the intervals of 1–5. All statistical analyses were performed with SPSS version 25, Mann-Whitney test was applied for comparison of satisfaction levels between patients from rural and urban areas (? = 0.05). Results: Patient satisfaction scores were high for both empathy and responsiveness averaged over rural (empathy 3.95 ± 0.715; responsiveness 3.93 ± 0.722) and urban areas (empathy 4.30 ± 0.640; responsiveness 4.28 ± 0.655). There were no significant regional differences for either dimension of patient satisfaction (p > 0.05), although mean scores tended to be higher among urban participants. Conclusion: Overall, RSGM Unmul has excellent performance in the aspect of empathy and responsiveness on dental healthcare service management resulting in high patient satisfaction levels.